A Chromosome-Scale Assembly of the Wheat Leaf Rust Pathogen Puccinia triticina Provides Insights Into Structural Variations and Genetic Relationships With Haplotype Resolution - Wu, Jing Qin; Song, Long; Ding, Yi; Dong, Chongmei; Hasan, Mafruha; Park, Robert F. (Frontiers in Microbiology, 2021)
Despite the global economic importance of the wheat leaf rust pathogen Puccinia triticina (Pt), genomic resources for Pt are limited and chromosome-level assemblies of Pt are lacking. Here, we present a complete haplotype-resolved genome assembly at a chromosome-scale for Pt using the Australian pathotype 64-(6),(7),(10),11 (Pt64; North American race LBBQB) built upon the newly developed technologies of PacBio and Hi-C sequencing. PacBio reads with ~200-fold coverage (29.8 Gb data) were assembled by Falcon and Falcon-unzip and subsequently scaffolded with Hi-C data using Falcon-phase and Proximo. This approach allowed us to construct 18 chromosome pseudomolecules ranging from 3.5 to 12.3 Mb in size for each haplotype of the dikaryotic genome of Pt64. Each haplotype had a total length of ~147 Mb, scaffold N50 of ~9.4 Mb, and was ~93% complete for BUSCOs. Each haplotype had ~29,800 predicted genes, of which ~2,000 were predicted as secreted proteins (SPs). The investigation of structural variants (SVs) between haplotypes A and B revealed that 10% of the total genome was spanned by SVs, highlighting variations previously undetected by short-read based assemblies. For the first time, the mating type (MAT) genes on each haplotype of Pt64 were identified, which showed that MAT loci a and b are located on two chromosomes (chromosomes 7 and 14), representing a tetrapolar type. Furthermore, the Pt64 assembly enabled haplotype-based evolutionary analyses for 21 Australian Pt isolates, which highlighted the importance of a haplotype resolved reference when inferring genetic relationships using whole genome SNPs. This Pt64 assembly at chromosome-scale with full phase information provides an invaluable resource for genomic and evolutionary research, which will accelerate the understanding of molecular mechanisms underlying Pt-wheat interactions and facilitate the development of durable resistance to leaf rust in wheat and sustainable control of rust disease.